The double-edged sword effect of performance pressure on public employees: The mediation role of mission valence - Sheng, Zhonghua; Fan, Bonai (Frontiers in Psychology, 2022)
Performance pressure is a unique stressor in the public sector. Prior studies revealed that it could be a challenge that stimulates functional behavior (i.e., vigor and dedication) or a threat that leads to dysfunctional consequences (i.e., exhaustion and depersonalization). But these articles failed to provide an integrated theoretical model to explain both phenomena simultaneously. We introduced the double-edged sword effect (also called the “too-much-of-good-thing” effect) of performance pressure to fill this theoretical gap. Furthermore, the mediation role of mission valence was examined to explore the buffet mechanism toward this nonlinear relationship. We collected 1161 valid questionnaire data from snowball sampling to test the research model. Our results revealed that: (1) performance pressure had an inverted U-shaped relationship with dedication and mission valence; (2) performance pressure hurt vigor rather than the curvilinear relationship; (3) mission valence can mediate the inverted U-shaped relationship between performance pressure and dedication. These empirical findings give theoretical contributions and practical insights to public personnel management.